Today's isms : Communism, fascism, capitalism, socialism - Ebenstein, William 1910-1976 (Prentice-Hall, 1954)
From the preface: The major conflict of our age ist the struggle between aggressive totalitarianism and the free way of life. Not long ago the chief threat to liberty was fascism; today it is communism. This book is a discussion of the main representatives of each side - communism and fascism on the totalitarian side, capitalism and socialism on the democratic. The key approach in this book is through the way of life concept rather than trough one particular aspect; also the psychological roots are given close attention.